Agregata cerastium subtrofilorum in C. sylvaticum na jugovzhodem obrubju Alp = Agregati Cerastium subtriflorum i C.sylvaticum na jugoistočnom rubu Alpa : doktorska disertacija - Vreš, Branko (Ljubljana-Zagreb : B. Vreš, 1996)
Sažetak: Agregati Cerastium subtriflorum i. C. sylvaticum na jugoistočnom rubu Alpa Vrstu Cerastium sylvaticum opisali su Waldstein i Kitaibel 1802. godine. Nekoliko godina kasnije biljku s manjim cvjetovima Kitaibel opisuje kao vrstu Cerastium umbrosum (Kanitz 1863). Ovoj vrsti pripisivane su različite taksonomske kategorije (Schur 1871, Richter & Guerke 1897, Hegi 1912, Hayek 1924, Gartner 1939). Pokazalo se da se vrsta C. umbrosum može pripojiti vrlo varijabilnoj C. sylvaticum. Primjerke sabrane od strane Freyera na Mangartu (Julijske Alpe), i poslane na određivanje Reichenbachu 1842. godine, ovaj prepoznaje kao novu svojtu - Cerastium subtriflorum. Svojtu rangira kao varijetet C. lanuginosum, za razliku od Pachera (1886) koji je smatra dobro diferenciranom i u Flori Koroške joj daje status vrste.
Mišljenja o svojti C. subtriflorum su, međutim, vrlo podijeljena. Na temelju primjerka iz Posočja, Beck 1908. godine opisuje vrstu C. sonticum koju kasnije citiraju i neki drugi autori. Godine 1939. Gartner izrađuje značajnu reviziju skupine. Svojtu C. umbrosum svrstava unutar vrste C. sylvaticum s rangom podvrste. Samo primjerke sabrane u visokim Alpama smatramo je vrstom C. subtriflorum. Beckovu vrstu C.sonticum je kao samostalnu vrstu odvojio od C. subtriflorum i podijelio u tri podvrste: tipičnu ssp. sonticum (Posočje), ssp. udinense (Furlanija-Julijska krajina) i ssp. savense (Zasavje). Ovu podjelu slijedi i nekoliko drugih autora. Gartnerova revizija osnivala se na morfološkoj analizi herbarskog materijala, ali čini se bez dostatnog uvažavanja velike varijabilnosti vrste C. subtriflorum.
U pedesetim godinama pojavljuju se sasvim drugačija stanovišta (Mayer 1954). Mayer zaključuje 1960. godine da C. sonticum nesumljivo pripada vrsti C. subtriflorum. Noviji botanički radovi Flora Europaea (Tutin et al. 1964) i Liste der Gefaessplanzen Mitteleuropas (Eherendorfer 1963, 1973) uključuju C. sonticum u vrstu C. subtriflorum, a C. umbrosum smatraju sinonimom za C. sylvaticum. Slično gledište imaju Pignatti (1982), Jalas & Suominen (1983), Wraber (1984) i Poldini (1991). Svrha ovog rada je morfološko i taksonomsko vrednovanje agregata Cerastium subtriflorum i C. sylvaticum na području jugoistočnih Alpa.
Ovo uključuje utvrđivanje dijagnostičke vrijednosti novih osobina ili njihovih kombinacija za razlikovanje svojti C. subtriflorum i C. sylvaticum, definiranje varijabilnosti tj. stabilnost pojedinih osobina, te njihove prisutnosti u pojedinim djelovima areala. Na temelju dobivenih rezultata želja je bila sistematski revudurati istražene svojte i herbarski materijal. Podaci o nalazištima (Tab. 2 i 3) iskorišteni su za izradu karata rasprostarnjenosti prema metodologiji kartiranja Srednje Europe (Sl. 9 i 10). Prema metodologiji kartiranja flore Europe dopunjene su UTM karte rasprostranjenosti preuzete iz Atlas Florae Europaeae (Jalas & Suominen 1983). S obzirom na problematiku skupine odabrana je odgovarajuća metodologija za obradu novosabranog i postojećeg herbarskog materijala (GJO, GZU, HEM, KL, LJU, LJM, TSB, W i WU).
Analizirano je više stotina primjeraka vrsta C.sylvaticum i C. subtriflorum. Materijal sabran prilikom terenskih istraživanja smješten je u radnoj zbirci - herbarij Biološkog inštituta ZRC SAZU u Ljubljani. Mjerene su morfološke osobine isključivo herbarskih primjeraka, a podaci su analizirani nekim novijim metodama numeričke taksonomije. Na više od 100 primjeraka izmjereno je 12 skupina morfoloških osobina: visina biljke, Duljina internodija cvata, duljina cvjetnih (plodnih) stapki, veličina lapova i latica, diljina ploda, veličina sjemnki i njihova papila. Osnovnom statističkom analizom obrađeno je 78 numeričkih parametara (Tab. 5-21) izabranih na temelju literarnih podataka, herbarskog materijala i istraživanja populacija na prirodnom staništu. Računani su T-testovi, koeficijenti varijabilnosti i korelacije.
Za testiranje 10 odabranih osobina (Tab. 23-25) upotrijebljana je diskriminantna analiza (klasifikacijski i postupno). Varijabilnodt pojedinih osobina (u%) prikazana je u tabelama (2 - 22), a za neke bitnije osobine i u obliku dijagrama (1-9). Najstabilnije osobine, često i s značajnim statističkim razlikama, pokazale su se duljina latica, visina biljke i omjer duljina/širina listova izdanaka. Nakon pregleda obimnog herbarskog materijala iz zbirki i prirodnih populacija, najboljim kvalitativnim osobinama pokazali su se oblik listova izdanka, njihove peteljke i dlakavost ruba na bazi latice vjenčića. Vrste C. sylvaticum i C. subtriflorum su vrlo srodne. U nekim populacijama obiju svojti, pogotovo na području Posavja i Posočja, primjerci koji rastu zajedno vrlo su slični u pojedinim osobinama. Uzrok ovakve sličnosti je vjerojatno introgresija gena.
Uzorak ovakve sličnosti je vjerojatno introgresija gena iz C. sylvaticum u vrstu C. subtriflorum. Primjerci C. subtriflorum, toga područja su zbog odgovarajućih mikroklimatskih uvjeta prilično slični primjercima C. sylvaticum s obzirom na veličinu i habitus (broj stabala, broj cvjetova, razgranjenost cvata). Zbog ove okolnosti nužna je osobita pozornost prilikom determinacije i razlikovanja ovih vrsta i poštivanja pojedinih dijagnostičkih osobina, tj. njihovih kombinacija (veličina biljke, duljina internodija stabljike i cvata, oblik listova izdanka, omjer duljina/širina lisne plojke i prisutnost peteljki, veličina listova stabljike, duljina dlaka narubu listova stabljike, veličina latica i obraslost trihomima, veličina sjemenki).Herbarski materijal različitihzbirki (GJO, GZU, KL, TSB, W, WU) je na temelju rezultata razvrstan i revidiran.
Na temelju rezultata može se zaključiti da su svojte C. sylvaticum i C. subtriflorum jasno izdiferencirane vrste koje se međusobno razlikuju na zadovoljavajućui način na osnovi slijedećih morfoloških osobina: veličina latica, dlakavost ruba na bazi latice, veličina biljke, razgranatost cvata, veličina i oblik listova izdanaka i njihovih peteljki. Ove se vrste razlikuju i po svojim ekološkim karakteristikama (tip staništa, vertikalna distribucija). Vrsta Cerastium Waldst. & Kit. je stanovnik sjenovitih kolinskih, submontanih i montanih šuma i šikara, pridova te obala potoka i rijeka. Uspjeva na vlažnom, humusnom tlu na nadmorskim visinama od 100 do 700 m. Vrsta C. sylvaticum je europski edem, rasprostranjena uglavnom u srednjoj i istaočnoj, djelomično i južnoj Europi. Biljke su visoke (20) 30-50 (70) cm, tamnozelene, s brojnim izdancima.
Listovi izdanaka su obično loptasti do okruglasti, uglavnom sa peteljkom. Rub listova stabljike pokriven je s (0,2) 0,4-0,7 (1,0) mm dugim dlakama. Cvat se grana 4-5 (7) puta i nosi brojne cvjetove (do 40). Latice vjenčića su (1) 1,4-1,8(2) puta duže od lapova, (4) 6-8 (10) mm duge, na bazi obrasle s 2-5 (ili više) dlaka. Vrsta Cerstium subtriflorum (Rchb.) Pacher raste u montanom, subalpskom i alpinskom pojasu (1000-2000 m), ali zalazi i u submontani pojas (200 - 500 m) nekih alpskih i predalpskih dolina. Pojavljuje se na alpskim travnjacima, vlažnim i sjenovitim pukotinama stijena planinskog pojasa i na šljunkovitim područjima alpskih i predalpskih dolina. Rasprostranjena je u istočnim Julijskim Alpama (Jalovško-Mangartska i Krnska skupina), srednjem dijelu Posočja i dio područja Zasavja (dolina rijeke Save ispod Kuma, dolina rijeke Gračanice).
Vrsta C. subtriflorum je stenoendem jugoistočnih Alpa. Biljke su visoke (7) 10-25 (40) cm, žutozelene boje, s manjim brojem izdanaka ili bez njih. Listovi izdanaka obično su jajasti ili lacentasti, sjedeći. Rub listova stabljike pokriven je s (o,5) 0,7-1,2 (1,4) mm dugim dlakama. Cvat se grana 2-3 (5) puta, cvjetova je manje (do 15), latice su (1,6) 2-2,5 (3) puta duže od lapova, (7) 8-12 (13) mm duge, na bazi uglavnom bez trihoma.
Summary: Cerastium subtriflorum and C. sylvaticum aggregats on the south-eastern margins of Alps Species Cerastium was defined by Waldstein and Kitaibel in 1802. A few years later Kitaibel described species Cerastium umbrosum (Kanitz 1863), which differed from the previous by smaller flowers. This species was ascribed a different taxonomic value by many authors (Schur 1871, Richter & Guerke 1897, Hegi 1912, Hayek 1924, Gartner 1939). It was found that it belongs into species C. sylvaticum, because it incorporates well in its wide variability. In 1842 Reichenbach identified a new taxon Cerastium subtriflorum on specimens from Mangrt (The Julian Alps), which were sent to him by Freyer, and characterized it as a variety of species Cerastium lanuginosum.
Pachner (1886) considered it a good species, therefore he elevated it to the species range in the flora of Koroška region (Carinthia).ertheless, the opinions of authors who reffered to the taxon in their works were very heterogeneous. On the basis of plants found in the Soea Valley Beck in 1908 described species Cerastium, which was later considered by several other authors. In 1939 Gartner made a thorough revision. He classified taxon C. umbrosum as a subspecies of C. sylvaticum. In species C. subtriflorum he ranged only altomontane specimens from the Alps. He divided Beck's species C. sonticum into three subspecies: a typical ssp: sonticum thriving in the Soea Vally, ssp. udinense growing in Furlanija-Julijksa krajina (Friuli-Julian March) and ssp. savense, only found in the Zasavje region.
His revision was founded on rigid morphological research of herbarium material, and he did not pay enough regared to variability of species C. subtriflorum. Some authors still fallow his classification, but diverse opinions appeared already in the fifities (Mayer 1954). In his treatise on endemic vascular plants Mayer in 1960 concluded that taxon C. sonticum doubtlessy belonges to species C. subtriflorum. In principal botanic works of recent time, Flora Europea (Tutin et al. 1964) and Liste der Gefaesspflanzen Mitteleuropas (Ehrendorfer 1963, 1973), taxon C. sonticum is incorporated in species C. subtriflorum, while C. umbrosum is treated as a synonym of species C. sylvaticum. Today many other authors (Wraber 1984, Pignatti 1982, Jalas & Suominen 1983, Poldini 1991) share this viewpoint.
The emphasis of our work was laid on morphological and taxonomic evaluation of Cerastium subtriflorum and Cerastium sylvaticum aggregats on the south-eastern margins of the Alps, and thus indirectly in the whole distribution area of both taxa. We tried to establish the following: According to which so far known and new morphological characteristics or their combinations can we differentiate the taxons mentioned? What is the variation scale of an individual character and its significance, as well as its reliability and usefulness when diferentiating or identifying individual taxa? What is the distribution of taxa in the research area and in the whole distribution area like? Our aim was also to evaluate systematically the taxa treated and to make a corresponding revision of existant herbarium material available.
Data on localite (Tab. 2 and 3) are presented in maps of taxa distribution according to Central European method of floristic mapping (Fig.9 and 10). Maps of taxa distribution are complemented according to method of European floristic mapping (UTM) applied in Atlas Flore Europaeae (Jalas & Suomionen 1983). In view of the subject defined we have chosen appropriate methods for the treatment of herbarium material. A considerable part of plants was gathered by us in the field (research area), and major part of the material surveyed comes from different national and foreign herbarium collections.
When researching taxa C. sylvaticum and C. subtriflorum, we surveywd handreds of plant specimes in nature, in herbarium collections of GJO, GZU, HEM, KL, LJU, LJM, TSB, W and WU, and those gathered on our own for the working herbarium of the Biological Institute of the Scientific Research Centre at the Slovene Academy of Science and Arts (ZRC SAZU) in Ljubljana. Measuring was accomplished on herbarium material only. The basis was morphological analysis of individual characters by some recent methods of numerical taxonomy.
On more than 100 different specimens we performed measurements for 12 groups of different morphological characters: plant size, length of stem internodes, sizee of stem leaves, size of stolone leaves, size of bract leaves in floral region, length of floral region internodes, length of floral and fruit pedicels, size of calyx leaves, size of corolla leaves, length of ripe fruit, seed size and papillas size. In basic statistic analyses we researched 78 different numerical parametres (Tables 5-21), subjecting them to test of statistically significant differences (T-test). We figured out also the coefficients of variability and correlation. By ten characters (Tables 23-25) we applied the multivitamine statistic method (classification analysis and successive discriminant analysis).
Variability of individual characteristics expressed in percents is shown in tables (5-22) and for more important characteristics also in the form of diagrams (1-9). The following characters turned out to be the least variable attributes which show statistically significant differences: length of corolla leaves, plant size and proportion length/width of stolone leaves. After surveying vast herbarium material and many populations in nature, from and petiolation of stolone leaves and hairiness at the bottom of corolla leavesappeared to be the most appropriate among qualitative characters. Species C. sylvaticum and C. subtriflorum are closley related, Therefore the similarity between some populations of plants C. subtriflorum and C.sylvaticum is very big, especially when they grow together (the Sava Vally, the Soea Vally).
One of reasons is probably the gene introgression of species C. sylvaticum into C. subtriflorum. Due to favorable microclimatic conditions in this area specimens of C. subrtiflorum are very similsr to plants of C. sylvaticum by size and branching (numerous stems, many flowers), therefore special carefulness is requested when making a distinction between specimens of both species. For precise determination we should take intoconsideration every individual differential character (plant size, length of stem internodies and floral region internodes, stolone leaf shape, proportion between their length, width and petiolation, size of stem leaves, length of hairs on leaf margin, corolla size, hairiness seed size) and their combinations.
On the basis of our research and conclusion we made a corresponding classification and revision of greater part of herbarium material from collections (GJO, GZU, KL, TSB, W, WU). We can draw a conclusion that species C. sylvaticum and C. subtriflorum differ well in combination of the following morphological characters: size of corolla leaves, hairiness on the margin at the bottom of corolla leaves, plant size, number of branches in floral region, size, shape and petiolation of stolone leaves. The ecological characteristics of both species (habitat type, vertical distribution) are different, too. Cerastium sylvaticum Waldst. & Kit. is a species of lowland, submontane and montane shady forests, bushes, gravels and sendbanks of rivulets and rivers. It thrives on humid humus soils at an altitude from 100 to 700 m above the sea level.
It is European endemic species, widespread above all in Central, eastern and partly southern Europe. Plants are (20) 30-50 (70) cm high, dark green with many stolones. Stolone leaves are usually spatilate to orbicular, mostly petiolate. The margins of stem leaves are overgrown with (0,2) 0,4-0,7 (1,0) mm long hairs. Inflorescence consists of 4-5 (7) branches with numerous flowers (up to 40). Corolla leaves are (1) 1,4-1,8 (2) times longer than calyx, (4) 6-8 (10) mm long, at the bottom generally overgrown with 2-5 (or more) hairs. Cerastium subrtiflorum (Rchb.) Pacher is a species with the centre of thriving in montane, sub-Alpine and Alpine belt (at the altitude from 1000 to 2000 m), but it can appear also in submontane belt (200 to 500 m) of some Alpine and per-Alpine vallys.
It grows in altimontane grasslands, in sub-Alpine and Alpine screes and in humid rocky channels as well as in rublles and gravels in Alpine and pre-Alpine vallys. Its distribution area includes eastern Julian Alps (Jalovec-Mangrt and Krn groups), the central Soea Vally and a part of the Sava Vally (at the foot of Kum and in the Graencia Valley). C. subtriflorum represents a conservative endemic species of south-limestone Alps. It is (7) 10-25 (40) cm high, yellow green plant. Stolones are less frequent and sometimes absent. Stolone leaves are usually ovate to lanceolate, sessile. The margins of stem leaves are overgrown with (0,5) 0,7-1,2 (1,4) mm long hairs. Inflorescence consists of 2-3 (5) branches, flowers are less numerous (up to 15).
Corolla leaves are (1,6) 2-2,5 (3) times longer than the calyx, (7) 8-12 (13) mm long, at the bottom almost always hairless.
Doktor prirodnih znanosti - biologija
Sveučilište u Zagrebu, Prirodoslovno-matematički fakultet, Ljubljana-Zagreb, 1996
Bibliografija: str. 140-142
Summary